GLUCOSAMINE INOSITOLPHOSPHORYLCERAMIDE TRANSFERASE1 (GINT1) Is a GlcNAc-Containing Glycosylinositol Phosphorylceramide Glycosyltransferase. Issue 3 (14th May 2018) - Ishikawa, Toshiki; Fang, Lin; Rennie, Emilie A.; Sechet, Julien; Yan, Jingwei; Jing, Beibei; Moore, William; Cahoon, Edgar B.; Scheller, Henrik V.; Kawai-Yamada, Maki; Mortimer, Jenny C.
Abstract : GINT1 is shown to be an indispensable glycosyltransferase that facilitates the glycosylation of GlcNAccontaining glycosylinositol phosphorylceramides in rice, with a minor role in Arabidopsis. Abstract: Glycosylinositol phosphorylceramides (GIPCs), which have a ceramide core linked to a glycan headgroup of varying structures, are the major sphingolipids in the plant plasma membrane. Recently, we identified the major biosynthetic genes for GIPC glycosylation in Arabidopsis ( Arabidopsis thaliana ) and demonstrated that the glycan headgroup is essential for plant viability. However, the function of GIPCs and the significance of their structural variation are poorly understood. Here, we characterized the Arabidopsis glycosyltransferase GLUCOSAMINE INOSITOLPHOSPHORYLCERAMIDE TRANSFERASE1 (GINT1) and showed that it is responsible for the glycosylation of a subgroup of GIPCs found in seeds and pollen that contain GlcNAc and GlcN [collectively GlcN(Ac)]. In Arabidopsis gint1 plants, loss of the GlcN(Ac) GIPCs did not affect vegetative growth, although seed germination was less sensitive to abiotic stress than in wild-type plants. However, in rice, where GlcN(Ac) containing GIPCs are the major GIPC subgroup in vegetative tissue, loss of GINT1 was seedling lethal. Furthermore, we could produce, de novo, "rice-like" GlcN(Ac) GIPCs in Arabidopsis leaves, which allowed us to test the function of different sugars in the GIPC headgroup. This study describes a monocot GIPC biosynthetic enzyme and shows that its Arabidopsis homolog has the same biochemical function. We also identify a possible role for GIPCs in maintaining cell-cell adhesion.